Legal counseling for narcotics abuse prevention through village regulation legislation in village of Dagang Kerawan district of Tanjung Morawa regency of Deli Serdang - Nasution, Siti Nurahmi; Nasution, Eva Syahfitri; Sembiring, Rosnidar; Purba, M. Hadyan Yunhas; Robert (Talenta Publisher, 2020)
The number of narcotics abuse cases in Indonesia is increasing every year, so that it has become a national issue. The victims of narcotics abuse are just not spread in urban areas, yet the village areas are not excluded from the spread. Narcotics circulation also does not regard age, social level, and even gender. It is not seldom that the main target of narcotics circulation is the young generations; this fact indeed becomes a concern for every element in Indonesia, considering young generations are the pole of hope of a nation. The village is a strategic area for the smuggling and circulation of narcotics abuse. To overcome the circulation and abuse of narcotics, therefore anticipation through policy and prevention strategy by legislating a legal rule according to a local government's authority. The lack of knowledge in formulating policy through legislation as a legal rule for preventing narcotics circulation and abuse constitutes this counsel to Dagang Kerawan Village people. By providing legal counselling about narcotics abuse prevention through village regulation legislation, it is hoped to prevent, reduce, and eradicate narcotics abuse and circulation, especially in villages.